fMRI research in the information concealment paradigm: data on cerebellar activity - Orlov, V.A.; Kartashov, S.I.; Malakhov, D.G.; Kovalchuk, M.V.; Alexandrov, Y.I.; Kholodny, Y.I. (Èksperimentalʹnaâ psihologiâ, 2025)
Context and relevance. The article continues a series of publications on the topic of forensic psychophysiology, in particular, in the field of neurocriminology. During the first cycle of studies, based on the obtained fMRI data, an analysis of the functional connectivity of various brain areas was undertaken, which resulted in the discovery of activity in a number of cerebellar areas when diagnosing the presence of concealed information (DPCI) about past events in a person. Objective. It is necessary to consider in more detail the dynamics of cerebellar activity at the individual level during DPCI. Hypothesis. Cerebellar activity is associated with the personal significance of the updated information. Methods and materials. The study presents data on a male sample of 23 people, technical university students aged 21-23. The data were obtained in experiments with the simultaneous use of fMRI and an MRI compatible polygraph MRIcP, modeling a person's concealment of personally significant information. Results. Experimental studies have confirmed the involvement of the cerebellum in neurocognitive processes that provide DPCI, and have also shown the relative autonomy of this structure's participation in the differentiated assessment of perceived stimuli by their significance under the conditions of the study. Conclusions. Cerebellar activity potentially can be used as an independent and relatively self-sufficient "marker" used to assess human brain activity at an individual level, suitable for DPCI. Контекст и актуальность. Статья продолжает цикл публикаций по теме криминалистической психофизиологии, в частности - в области нейрокриминалистики. В ходе первого цикла исследований на основе полученных фМРТ-данных был предпринят анализ функциональной связности различных зон мозга, по итогам которого была обнаружена активность ряда зон мозжечка при диагностике наличия у человека скрываемой им информации (ДНСИ) о событиях прошлого. Цель. Требуется подробнее рассмотреть динамику активности мозжечка на индивидуальном уровне в ходе ДНСИ. Гипотеза. Активность мозжечка связана с личностной значимостью актуализируемой информации. Методы и материалы. В исследовании приведены данные по мужской выборке 23 человек, студентов технического вуза, в возрасте 21-23 лет. Данные были получены в экспериментах с одновременным применением фМРТ и МРТ-совместимого полиграфа (МРТсП), моделировавших сокрытие человеком личностно значимой для него информации. Результаты. Экспериментальные исследования подтвердили вовлеченность мозжечка в нейрокогнитивные процессы, обеспечивающие ДНСИ, а также показали относительную автономность участия этой структуры в дифференцированной оценке воспринимаемых стимулов по их значимости в условиях проводимого исследования. Выводы. Активность мозжечка в перспективе может быть использована в качестве самостоятельного и относительно независимого «маркера», используемого в целях оценки активности мозга человека на индивидуальном уровне, пригодной для ДНСИ.